2020
DOI: 10.1177/0160017620931572
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pollution and Business Environment on Firm Productivity in Africa

Abstract: In this article, we explore the links between city competitiveness and air pollution and business environment. Because competitive cities not only attract more productive firms but also facilitate their business, we choose to look at firm performance as a proxy for city competitiveness. We particularly focus on African firms because this region is developing fast, experiencing increasing pollution levels and the effects of agglomeration economies. We find two interesting results. First, the negative associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The decrease in the number of tourists also happened in China [36], Cyprus, and Great Britain [35]. In addition, a negative correlation has been found between air pollution and the company's performance [14], and air pollution has been shown to harm human health [41]. In a similar manner, this study found the effect of small particulate matter on products/services and operations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The decrease in the number of tourists also happened in China [36], Cyprus, and Great Britain [35]. In addition, a negative correlation has been found between air pollution and the company's performance [14], and air pollution has been shown to harm human health [41]. In a similar manner, this study found the effect of small particulate matter on products/services and operations.…”
Section: Discussionsupporting
confidence: 63%
“…Tourism brings income into the country, creating jobs, alleviating poverty, and encouraging the production of indigenous products, souvenirs, and services that are unique to the local area and which contribute to cultural preservation [1]. Factors influencing tourism consist of motivation [10], destination characteristics [11], convenience, and accessibility [12][13][14]. The World Tourism Organization describes tourism activities as comprising of accommodation and restaurants, transportation, travel agencies, and recreational activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of total factor productivity (TFP), Wang et al (2021) find that improvement in air quality in 105 Chinese cities leads to improvement in TFP. Soppelsa et al (2021), using a sample of African firms, report a negative association between air pollution and firm performance, which suggests that controlling air pollution can enhance a firm's overall productivity. These studies on labor productivity or overall firm productivity do not address the possible changes in the capital-labor ratio.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Consistently, Montalbano and Nenci ( 2019 ) provide some evidence supporting the ‘learning energy efficiency by exporting’ paradigm in some cases of a large sample of firms located in 30 Latin American and Caribbean countries. It is also important to note that the economic performance of enterprises may be obstructed by environmental problems (Soppelsa et al 2021 ) and improved by the commitment to environmental protection (Efobi et al 2019 ), which together favor the win–win strategy. Structural change capacity: Structural change, which is commonly evaluated by the comparisons of sectoral shares in the national economy, plays a decisive role in energy efficiency.…”
Section: Relevant Literaturementioning
confidence: 99%